Ketahanan Pembiayaan Kesehatan di Indonesia Melalui Integrasi Public Financial Management dan Strategic Purchasing dalam Jaminan Kesehatan Nasional - Fatima Tudzahro; Riswandy Wasir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to synthesize the relationship between Public Financial Management (PFM) and Strategic Purchasing in shaping health financing resilience and to develop a conceptual model for strengthening National Health Insurance (JKN) financing in Indonesia. This study used a literature review design with a thematic narrative synthesis approach applied to scientific articles, national official documents, and international policy documents selected through thematic inclusion criteria covering health financing, PFM, strategic purchasing, JKN, and universal health coverage, and analyzed narratively to identify patterns, inter-concept relationships, and policy gaps. The findings indicate that adaptive PFM strengthens health budget planning, allocation, fund disbursement, flexibility, and accountability, while strategic purchasing directs health spending through benefit design, provider contracting, payment methods, and performance and quality monitoring, such that their integration can strengthen allocative efficiency, payment responsiveness, service quality, financial protection, and JKN sustainability. This study concludes that health financing resilience in Indonesia requires the harmonization of fiscal regulation and health policy through the integration of adaptive PFM and effective strategic purchasing as the foundation for a sustainable JKN system. Keywords: Health Financing Resilience, Indonesia, National Health Insurance, Public Financial Management, Strategic Purchasing, Universal Health Coverage